(untitled) (International journal of artificial intelligence, 2025)
This article explores methods for developing problem-solving competence in physics education. In modern teaching, it is essential to cultivate students’ abilities to think independently, analyze problems, and find solutions in challenging situations. The article discusses problem-based learning, project-based instruction, experimental approaches, and interactive pedagogical technologies as effective ways to foster problem-solving skills in physics students.